Edukasi Literasi Digital dan Anti Hoaks bagi Pelajar dan Masyarakat di Era Informasi - Bani Nurhakim; Cep Lukman Rohmat; Reza Saputra; Rio Harsadino (CV. Multi Kreasi Media, 2022)
The development of information and communication technology has brought significant impacts on society, particularly in terms of access to information, communication, and online learning. However, this progress also comes with various challenges, especially concerning digital security, the spread of hoaxes, and the low level of digital literacy among students and the general public. The lack of ability to distinguish between valid and invalid information, as well as limited awareness of online ethics and safety, has become an urgent issue that must be addressed through proper education. This Community Service Program (PKM) aims to improve digital literacy through training on internet safety and anti-hoax education for students and the local community in the partner area. The method used involves a participatory educational approach through seminars, interactive discussions, case studies, and simulations of information source verification. The training materials cover recognizing hoaxes and disinformation, using credible information sources, maintaining digital privacy, and practicing ethical communication on social media. The results of the program showed a significant increase in participants’ knowledge regarding hoax characteristics, fact-checking techniques, and the importance of maintaining a responsible digital footprint. Participants also became more critical in consuming information and demonstrated behavioral changes in using the internet safely and responsibly. This training not only enhances individual capacity but also strengthens social resilience in facing the flow of information in the digital era. This program is expected to serve as a sustainable effort in fostering a culture of healthy and wise digital literacy, and it can be replicated in schools and other communities to broaden its impact.